(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
The main mechanism of human infection is nutritional, contact and household. Human infection occurs through contact with the fur of animals that host helminths (often dogs), when picking berries and herbs, drinking water from contaminated sources, eating vegetables and fruits contaminated with feces of the definitive host (for example, a dog). Susceptibility is universal, however, persons in certain professions or lifestyles associated with animal husbandry (slaughterhouse workers, shepherds, tanners, hunters and others) are at high risk.